2007
DOI: 10.4314/ejhd.v20i2.10022
|View full text |Cite
|
Sign up to set email alerts
|

Child labor and childhood behavioral and mental health problems in Ethiopia

Abstract: Background: According to ILO estimates, at least 180 million children aged 5 to 14 years are currently engaged in fulltime work in the developing countries. However, very little information exists about childhood behavioral and mental disorders in Ethiopia. Objective: The objectives of this study are to estimate the prevalence and describe the nature of behavioral and mental health problems, as well as child abuse, nutritional problems, gross physical illness and injury among child laborers aged 8 to 15 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 8 publications
3
27
0
Order By: Relevance
“…In this study, a significant number of people implicated supernatural powers as causing mental health problems which is in agreement with other studies conducted in Ethiopia (13,14). Such traditional notions whereby supernatural powers are attributed to controlling the well being of an individual's mind are widespread in all ethnic or religious groups in Ethiopia (15). Similar results were also observed in other African studies (16,17).…”
Section: Discussionsupporting
confidence: 86%
“…In this study, a significant number of people implicated supernatural powers as causing mental health problems which is in agreement with other studies conducted in Ethiopia (13,14). Such traditional notions whereby supernatural powers are attributed to controlling the well being of an individual's mind are widespread in all ethnic or religious groups in Ethiopia (15). Similar results were also observed in other African studies (16,17).…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, Table 4 shows that 39.1% of respondent often had the experience of headache, while 27.3% respondents sometimes had headache. These findings correlate with the findings of Alem et al (2006) who have reported frequent headache among children engaged in child labour. Likewise, according to the study of Mohamed et al (2009), child labourers generally experience several health problems due to their labour work such as breathing problems, skin diseases, physical pain, eyesight problems and mental disorders.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…Although the intervention was associated with reduced aggressive behaviours and overall mental health problems among females, there was no effect on mental health indicators among male participants. Available studies conducted in small populations across Ethiopia show a wide-ranging prevalence of mental health problems, varying from 5.5% [28] to 49% of non-at-risk youth reporting mental disorders or mental distress [29]. A key message is that it appears that separation from family is associated with higher levels of mental health problems among young people [30].…”
Section: Discussionmentioning
confidence: 99%